Eye on fashion - Hanekom, Henrietta Hughes (Bloemfontein: Central University of Technology, Free State, 1991)
"LOOKING BACK AT FASHION PHOTOGRAPHY WE SEE THAT THE WORLD IN WHICH WOMAN HAVE MOVED, WORKED, SOCIALIZED AND BECOME INCREASINGLY LIBERATED IS CHRONICLED- ALTHOUGH SOMETIMES INADVERTENTLYALMOST AS ASSIDUOUSLY AS FASHION ITSELF. THROUGH FASHION PHOTOGRAPHY WE COLLECT A UNIQUE AND VALUABLE RECORD OF THE SOCIETY OF THE TIME, ITS MOODS AND ITS MANNERS AND CAN PERCEIVE THE CURRENT CULTURAL PREOCCUPATIONS- ARTISTIC INFLUENCES, THEATRICAL STYLES, SOCIAL TRENDS, THE CHANGING STYLES OF SALON AND NEWS PHOTOGRAPHY." (VOGUE BOOK OF FASHION PHOTOGRAPHY- POLLY DEVLIN 1979 THE CONDe NAST PUBLICATIONS LTD. FIRST PAPERBACK EDITION 1984). THE GREAT INTEREST IN FASHION PHOTOGRAPHY TODAY IS A SYMPTOM OF PEOPLE'S OBSESSION WITH POWER. THE GROWING POWER OF THE NEW WOMAN AND THE UNEXPECTEDLY ALL PERVADING POWER OF WORLD-WIDE FASHION AND THE ALL ENCOMPASSING POWER OF PHOTOGRAPHY WITH ITS CLONED IMAGE SPREADERS T.V. AND FILM. WHEN POWER IS PRESENT, MONEY CAN NOT BE FAR AWAY AND THE GROWTH OF FASHION PHOTOGRAPHY DEPENDED ON THE AMOUNT OF FASHION SELLINGS. THIS FASHION IMPRIMATUR WOULD NOT BE SUCCESSFUL WITHOUT THE MAIN INGREDIENT BEING SEX: THE ALL POWERFUL HUMAN MOTIVE FOR ACTION, THE HUMAN ENERGIZER WHICH MAKES PEOPLE LOVE, ACT, GIVE AND BUY. THROUGHOUT HISTORY THIS SEX SYMBOL HAS ALWAYS BEEN WOMAN. IN THE BEGINNING EVERYTHING WAS SIMPLE AND THE PURPOSE OF FASHION PHOTOGRAPHY WAS JUST TO SHOW WOMAN WEARING OUTFITS, BUT IT CHANGED AND THE WHOLE OPERATION WAS MADE COMPLEXED WHICH INVOLVED ART, TALENT, TECHNIQUE, PSYCHOLOGY AND SALESMANSHIP. FASHION IS A SYMBOL OF CLASS EDUCATION, TASTE, IMAGINATION AND SOMETIMES IT IS EVEN REVOLTING AND DARING. FASHION PHOTOGRAPHY PLAYED A VERY IMPORTANT ROLE IN THE EMANCIPATION OF WOMAN. NO OTHER GROUP OF HUMAN BEINGS HAVE EVER BEEN PORTRAYED SO EXTENSIVELY AND PUBLICLY, AND NO OTHER MEDIUM HAS REPRODUCED SO MANY VARYING IMAGES OF WOMAN AS WOMANS'MAGAZINES. IF A PERSON SHOULD PUT TOGETHER ALL THE ADVERTISING AND EDITORIAL PHOTOGRAPHS THAT HAVE BEEN PUBLISHED OF FASHION AND PERSONALITIES, THE TOTAL IS STAGGERING. TODAY, FASHION PHOTOGRAPHY HAS TO PORTRAIT "REAL" WOMAN WITH A PURPOSE TO THE WOMANS'LIVES, IT HAS TO SHOW- BY THE WOMAN'S MOVEMENT AND EXPRESSIONS THAT SHE IS INVOLVED IN AN ACTIVE AND INTELLIGENT LIVE. THE NEW AWARENESS OF THE MODERN WOMAN HAS TO SHOW THROUGH IN THE FASHION PHOTOGRAPHS. A STUPID BEAUTY HAS NO APPEAL. THROUGH THE SENSITIVE SUBTLETY OF GOOD FASHION PHOTOGRAPHERS, QUALITIES NEEDED TO BRING THESE NEW AWARENESSES OF THE MODERN WOMAN FORWARD, ARE ENTRAPPED. IN THE HISTORY OF FASHION PHOTOGRAPHY UNFORGETTABLE IMAGES HAVE ALREADY BEEN CREATED BY A FEW EXTRAORDINARY ARTISTS OF THE CAMERA. SOME EXAMPLES ARE: BARON DE MEYER, STEICHEN, BEATON, HUENE HARST, FRISSELL, PENN, AVEDON, KLEIN, BOURDIN, NEWTON, ELGORT, TURBEVILLE AND LARTIGUE. PHOTOGRAPHY IN GENERAL IS AN ANONYMOUS MEDIUM AND THE TRIUMPHS OF THESE FEW GREAT PHOTOGRAPHERS CAN BE BECAUSE OF THE OBSESSIVE, UNSHAKABLE AND PERSISTENCE IN EXPRESSING AND CREATING A PERSONAL STYLE AND VISION. WITH THE EVOLUTION OF WOMEN ' S ATTITUDES THE TRICKS OF THE OLD- FASHIONED SEDUCTION ARE SLOWLY DISAPPEARING AND A HEALTHY ENERGETIC, FLIRTING IMAGES HAVE REPLACED THAT OF THE HYPNOTIZING SEDUCTIVENESSES. IN COMMUNICATING WITH THE READER, IN REVEALING INTIMACY, WOMAN FASHION PHOTOGRAPHERS HAVE PLAYED VITAL ROLES FOR MEN ARE MORE CONCERNED WITH STRUCTURE, COMPOSITION, STRENGTH AND FORM. WOMAN ARE MORE SENSITIVE TO FORM BUT THEY ARE ABLE TO SEE DEEPER AND MORE IN HARMONY WITH THE ESSENCE OF FEMININITY. THE EMERGENCE OF WOMAN FASHION PHOTOGRAPHERS COMES AT A TIME IN FASHION PHOTOGRAPHY WHEN FASHION IS MORE FLUID AND LESS STRUCTURED. WOMAN TODAY WANT TO MOVE IN THEIR ACTIVE LIFE STYLES AND THEIR CLOTHES ARE NO LONGER THE STRAIGHT JACKETED CORSETED,PRESKETCHED GARMENTS THAT ONCE ENTRAPPED WOMAN. THIS REVOLT OF WOMAN AGAINST THAT OF A MAN-IMPOSED IMAGE HAS BEEN CAUGHT BY WOMAN PHOTOGRAPHERS WHO KNOW HOW TO PORTRAY THE MULTIPLE MOODS OF WOMAN. WOMEN PHOTOGRAPHERS ALSO KNOW THE SECRETS OF TENDERNESS ,THAT GOD-GIVEN POWERS TO SOOTHE AND TO LOVE WHICH ARE THE ANSWERS TO THE GREAT SUBCONSCIOUS LONGINGS OF BOTH MEN AND WOMEN. PHOTOGRAPHERS TODAY,BECAUSE OF THEIR INVOLVEMENT AND AWARENESS OF TECHNICAL MEANS, CAN PORTRAY IMAGES USUALLY UNSEEN OR BARELY SEEN BY THE HUMAN EYE AND PERHAPS MORE BEAUTIFUL THAN THE EVERYDAY VISIBLE-HAS CREATED A NEW EXPERIENCE. MODELS'HAIR IS NOW CAUGHT IN MOMENTS OF ABANDONING IN SPACE,BODIES FLY,RUN AND MOVE UNEXPECTEDLY WITHIN THE FRAMES AND WHICH REVEAL WOMAN AT THEIR MOST INTENSE MOMENTS OF BEING. BOTH MEN AND WOMEN HAVE BUILT IN-PSYCHOLOGICAL URGES TO OBSERVE AND GLORIFY THE BEAUTY OF WOMEN AND THE PART OF WOMENS'ETERNAL ROLE IS TO STIMULATE EROTIC DESIRE AND THIS CAN BE ACHIEVED, IN A FASHION PHOTOGRAPH THROUGH THE MODEL, HER CLOTHES,MAKE-UP AND HAIR. THE PHOTOGRAPHER,IN A SITTING,HAS TO INTENSIFY THESE AREAS OF APPEAL. FASHION PHOTOGRAPHY ATTEMPTS TO PORTRAY THE ARCHETYPAL WOMEN AND THESE IMAGES VARIES AT DIFFERENT MOMENTS OF HISTORY.JUST AS FASHION CHANGES,OUR TASTE IN FEMININE BEAUTY ALSO CHANGES AND EACH ERA HAS ITS OWN DESIRES. TODAY FOR AN EXAMPLE THE MODELS ARE VERY YOUNG FOR THE CAMERA AGES PEOPLE QUICKLY AND A SIXTEEN YEAR OLD OR EVEN AN EIGHTEEN YEAR OLD MODEL COULD EASILY BE SEEN THROUGH THE EYE OF THE CAMERA AS A THIRTY YEAR OLD. YOUTH,ENERGY AND AN INNER DYNAMIC QUALITY ARE ALSO ESSENTIAL QUALITIES FOR THE MAKING OF A GREAT MODEL. THE AUTHOR THROUGH THIS ,A STORY OF FASHION PHOTOGRAPHY WOULD LIKE TO LEAD THE READER THROUGH THE FASHION INDUSTRY AS THE AUTHOR SEES IT AND WOULD LIKE THE READER TO HAVE A CLEAR VISION OF THE HISTORY AND THE GREAT LEADERS AND THE AUTHOR WOULD LIKE TO DISCUSS AND SHOW SOME OF THE AUTHORS'OWN WORK.
Thesis
Keywords: Photographs; Fashion photography; Photography - Study and teaching - South Africa